The discongruence index, a simple predictor of cardiac remodeling after transcatheter aortic valve replacement. (14th October 2021) - Islas, F; De Agustin, A; Jimenez, P; Nombela, L; Marcos Alberca, P; Seabra, D; Olmos, C; Lepori, A; Mahia, P; Perez De Isla, L
Abstract: Background: Aortic stenosis causes several changes in left ventricular (LV) geometry and function; cardiac remodeling after transcatheter aortic valve replacement (TAVR) is variable among patients and it is not clearly defined. The aim of this study is to identify factors associated with LV functional and structural recovery. Methods: 428 patients were retrospectively studied; all patients underwent transthoracic echocardiography prior to TAVR; specific measurements such as maximum internal diameter of the prosthetic valve, nominal loss and percentage of nominal loss regarding to valve size, as well as the discongruence index (Prosthesis size/BSA) were evaluated at discharge and 1-year follow up. Positive cardiac remodeling (PCR) was considered if patients had a reduction of ≥20% of left ventricle mass index (LVMi) and ≥10% of end-diastolic volume index (LVEDVi). Results: Mean age of the cohort was 83±5.6 years, 55% were female (n=236), mean aortic valve area was 0.7±0.2cm 2 ; mean LVMi and LVEDVi were 129.4±35.4gr/m 2 and 54.5±22ml/m 2 respectively. LVMi reduction ≥20% was observed in 30% (n=128) of patients; LVEDVi reduction ≥10% was observed in 44% (n=188) of patients. A total of 107 patients (25%) showed PCR. Female patients showed more PCR (p=0.04). Discongruence index was significantly higher in patients with PCR (15.5±1.9 vs 14.5±1.8, p=0.01) and was significantly associated to LVMi (121.5±28.9 vs 150.8±41.1g/m 2 ) and LVEDVi individually (55.1±17.2 vs 42.7±16.7ml/m 2 ; p<0.01). Left ventricular ejection fraction (LVEF) had a statistically significant increase among patients with PCR (53.2±14.9 vs 56.7±11.5, p=0.04) global longitudinal strain showed improvement at 1-year follow-up as well, although not statistically significant (−17.3±3.7 vs −18.3±3.4 p=0.53). Conclusions: The discongruence index is a simple and feasible parameter that can predict positive cardiac remodeling after TAVR which can have a significant impact in clinical outcome of patients. Funding Acknowledgement: Type of funding sources: None.